Cave Communities: From the Surface Border to the Deep Darkness - Manenti, Raoul; Lunghi, Enrico (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
From a biological perspective, the subterranean realm is one of the less studied, but at the same time, one of the most promising, theatres for new findings and research. Compared to those on the surface, the ecological conditions occurring in subterranean habitats are relatively simple, and this may be an optimal scenario for understanding the mechanisms allowing the colonization, adaptation, and evolution of species, as well as their interactions within local communities. Diversity in subterranean habitats is often overlooked, and few studies embrace whole communities or try to assess functional relationships between species. This Special Issue reprint comprises papers covering a wide range of aspects related to the distribution, composition, and roles of subterranean communities occurring in different typologies of subterranean habitats.